PROSES REAKTIVASI TANAH PEMUCAT BEKAS SEBAGAI ADSORBEN UNTUK PEMURNIAN MINYAK SAWIT KASAR DAN BIODIESEL - Ani Suryani, Gustan Pari dan Amelia Aswad TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Spent Bleaching Earth (SBE) is a solid waste material generated as a part of the refining process in frying oil industry. Large quantity of SBE is disposed in landfills, causing fire and environmental hazards due to its substantial oil content. There is a need for a process to recoverit. The high content of the oil represents a high potential as material for biodiesel production. The purpose of this research was to obtain the best method of SBE reactivation to reuse it as an adsorbent for refining of Crude Palm Oil (CPO) and biodiesel. SBE could be reused with reactivation by acid activation and heat treatment. SBE was activated by various types of acids (H3PO4 2%, HNO3 5%, and H2SO4 10% (v/v)) and various ratio (1:1, 1:2, and 1:3 (w/v)) at temperature of 400°C. Measurements of quality of Reactivated Bleaching Earth (RBE) were carried out by adsorption of colour pigments from degummed palm oil. Bleaching efficiency of RBE was determined by measuring the absorbance value of oil that has been bleached with RBE. The experimental results indicated that treatment of SBE with HNO3 5% (1:2) was the best condition and produced material which most effective in removing coloured pigments from CPO. This best condition was used to five times repetitive reactivation process. The ability of each RBE would be applied for the purification of biodiesel and CPO. Measurements of various quality parameters of biodiesel and CPO were carriedout. They included free fatty acid, iodine value, density, viscosity, bleaching efficiency, and % T. The results showed that the quality of bleached palm oil and biodiesel increased after bleaching with RBE.Keywords: spent bleaching earth (SBE), reactivated bleaching earth (RBE), crude palm oil (CPO), biodiesel,reactivation, bleaching efficiency